Complete biliary obstruction without jaundice due to an anatomic variation - Ödemiş, Bülent; Köksal, Aydın Şeref; Torun, Serkan; Yurdakul, Mehmet; Kayaçetin, Ertuğrul (Turkish Journal of Gastroenterology, 2014)
Abstract An aberrant right posterior hepatic duct is present in 4.8-8.4% of the population. It is one of the causes of bile duct injury during laparascopic cholecystectomy. Herein we present a patient with complete transection of the common hepatic duct during laparascopic cholecystectomy (Stewart-Way class 3). Interestingly, the patient had an intact aberrant right posterior duct draining into the common hepatic duct distal to the obstruction site that prevented early diagnosis of the biliary injury because of drainage of the liver sufficient to prevent the development of jaundice.